2015
DOI: 10.1001/jama.2014.17942
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MR/Ultrasound Fusion–Guided Biopsy With Ultrasound-Guided Biopsy for the Diagnosis of Prostate Cancer

Abstract: Importance Targeted magnetic resonance (MR)/ultrasound fusion prostate biopsy has been shown to detect prostate cancer. The implications of targeted biopsy alone vs standard extended-sextant biopsy or the 2 modalities combined are not well understood. Objective To assess targeted vs standard biopsy and the 2 approaches combined for the diagnosis of intermediate- to high-risk prostate cancer. Design, Setting, And Participants Prospective cohort study of 1003 men undergoing both targeted and standard biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
905
10
21

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,365 publications
(980 citation statements)
references
References 28 publications
44
905
10
21
Order By: Relevance
“…The combination of systematic and targeted biopsies (MRI-Tbx) may also better predict the final GS [29]. As a result, some authors proposed performing systematic mpMRI before prostate biopsy [30,31]. One metaanalysis suggested that MRI-Tbx had a higher detection rate of clinically significant PCa compared to TRUS biopsy (sensitivity 0.91 vs. 0.76) and a lower rate of detection of insignificant PCa (sensitivity 0.44 vs. 0.83).…”
Section: Prostate Biopsymentioning
confidence: 99%
“…The combination of systematic and targeted biopsies (MRI-Tbx) may also better predict the final GS [29]. As a result, some authors proposed performing systematic mpMRI before prostate biopsy [30,31]. One metaanalysis suggested that MRI-Tbx had a higher detection rate of clinically significant PCa compared to TRUS biopsy (sensitivity 0.91 vs. 0.76) and a lower rate of detection of insignificant PCa (sensitivity 0.44 vs. 0.83).…”
Section: Prostate Biopsymentioning
confidence: 99%
“…However, the significance and extent of combined systematic biopsies remains controversial. Siddiqui et al detected after adding systematic to targeted biopsy in their cohort of 1003 patients with a positive mpMRI 29 (2.9%) additional csPCa cases [2]. That resulted in the significantly higher number of 35 patients needed to be biopsied additionally with the systematic approach to detect one csPCa case.…”
Section: Cancer 2016 Mar 15;122(6):884-92mentioning
confidence: 99%
“…Fusion of archived multiparametric MRI images with live transrectal US has allowed for improved diagnostics and targeting. A recent publication from the National Cancer Institute reported on 1003 men undergoing targeted and standard biopsies between 2007 and 2014 [23]. The primary objective was to compare detection of higher risk cancer of the prostate, with secondary objectives assessing detection of lower risk disease and predictive capabilities of fusion biopsies for whole gland pathology at time of radical prostatectomy.…”
Section: Editorialmentioning
confidence: 99%